2016
DOI: 10.5194/amt-9-4269-2016
|View full text |Cite
|
Sign up to set email alerts
|

1064 nm rotational Raman lidar for particle extinction and lidar-ratio profiling: cirrus case study

Abstract: Abstract. For the first time, vertical profiles of the 1064 nm particle extinction coefficient obtained from Raman lidar observations at 1058 nm (nitrogen and oxygen rotational Raman backscatter) are presented. We applied the new technique in the framework of test measurements and performed several cirrus observations of particle backscatter and extinction coefficients, and corresponding extinctionto-backscatter ratios at the wavelengths of 355, 532, and 1064 nm. The cirrus backscatter coefficients were found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 62 publications
3
93
0
Order By: Relevance
“…The wavelengthindependent backscatter coefficients of up to 3.5 Mm −1 sr −1 at cirrus center indicate peak particle extinction values of 100-120 Mm −1 . The extinction values are obtained by applying a multiple-scattering-corrected cirrus lidar ratio of 30-35 sr to the cirrus backscatter coefficients (Haarig et al, 2016b). The extinction measured with the Raman channels would need a too-large smoothing length in the thin cirrus.…”
Section: Case Study I: Comparison Of Polis and Bertha Observations (1mentioning
confidence: 99%
See 1 more Smart Citation
“…The wavelengthindependent backscatter coefficients of up to 3.5 Mm −1 sr −1 at cirrus center indicate peak particle extinction values of 100-120 Mm −1 . The extinction values are obtained by applying a multiple-scattering-corrected cirrus lidar ratio of 30-35 sr to the cirrus backscatter coefficients (Haarig et al, 2016b). The extinction measured with the Raman channels would need a too-large smoothing length in the thin cirrus.…”
Section: Case Study I: Comparison Of Polis and Bertha Observations (1mentioning
confidence: 99%
“…To contribute to this field of dust research, we redesigned and upgraded our multiwavelength polarization/Raman lidar BERTHA (Backscatter Extinction lidar-Ratio Temperature Humidity profiling Apparatus; Althausen et al, 2000;Haarig et al, 2016b). BERTHA has been used in nine field campaigns in Europe, Asia, and Africa from 1997 to 2008 Ansmann et al, 2002;Franke et al, 2003;Tesche et al, , 2011a.…”
mentioning
confidence: 99%
“…Using ground-based DIAL (differential absorption lidar; Weitkamp, 2008;Späth et al, 2016) water-vapor can be measured, which can even be combined with backscatter measurements to derive more details of aerosol particle properties (Wulfmeyer and Feingold, 2000). Lidar techniques based on the vibrational and rotational Raman effect, like RRL (rotational Raman lidar) allow for the measurement of trace gas profiles (Whiteman et al, 1992;Turner et al, 2002;Wulfmeyer et al, 2010;Haarig et al, 2016) as well as profiles of atmospheric temperature, particle backscatter cross section, particle extinction cross section, and particle depolarization properties (Behrendt et al, 2002;Hammann et al, 2015;Radlach et al, 2008). High-spectral-resolution lidar (HSRL) systems furthermore allow for cloud and particle characterization (Shipley et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (e.g., Tao et al, 2008;Lu et al, 2011;Ferrare et al, 2001;Müller et al, 2007;Haarig et al, 2016) investigated the LR for different atmospheric conditions and aerosol types, like dust in Groß et al (2011) and volcanic ash in Ansmann et al (2010). The studies showed that the LR is a highly variable parameter depending on the predominant aerosol.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%